Digital games and English vocabulary among eighth graders at a public institution in Loja. School year 2022-2023 - Cabrera Ponce, Valeria del Rocío (2023)
Vocabulary plays a crucial role in facilitating effective communication across all languages. Hence, it is important to implement innovative resources in order to facilitate EFL learners’ vocabulary learning. Therefore, this research aimed to increase vocabulary knowledge through digital games implementation among eighth graders at a public institution in Loja, during the 2022 – 2023 school year. In this sense, a mixed-method was employed, combining quantitative data analyzed through descriptive statistics and qualitative data interpreted through thematic analysis, using such data sources as pretest, posttest, mixed-type questionnaire, reflective journals and peer observations as data collection instruments. Consequently, significant differences between pretest and posttest mean scores were observed, indicating improvements in each vocabulary sub-indicator assessed, including associations, spelling, grammatical functions, collocations, and pronunciation, which means that digital game resources such as: Breshna, Factile, Gamilab, Mobbyt and Oddlu really improved EFL students’ vocabulary knowledge. In addition, students’ perceptions about the use of digital games to enhance vocabulary were highly positive, since the engaging and enjoyable nature of digital games increased their motivation, emotional involvement, active interaction, collaborative and critical thinking skills. In conclusion, the research results and findings demonstrated that digital games are an effective tool for enhancing students' English vocabulary. Keywords: Digital games, educational games, technological resources, vocabulary aspects